Identifying digital transformation paths in the business model of SMEs during the COVID-19 pandemic - Anjar Priyono; Abdul Moin; Vera Nur Aini Oktaviani Putri (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The objective of this study was to analyze how small and medium enterprises (SMEs) cope with environmental changes due to the COVID-19 pandemic by pursuing the business model transformation with the support of digital technologies. To achieve the objective, this study used a multiple case study design with qualitative analysis to examine the data obtained from interviews, observation, and field visits. Seven manufacturing SMEs from Indonesia were selected using a theoretical sampling technique, with the purpose of achieving some degree of variation to allow us to undertake replication logic. Our analysis demonstrates that SMEs adopt a different degree of digital transformations, which can be summarized into three paths, depending on the firms' contextual factors. First, SMEs with a high level of digital maturity who respond to the challenges by accelerating the transition toward digitalized firms; second, SMEs experiencing liquidity issues but a low level of digital maturity who decide to digitalize the sales function only; and, third, the SMEs that have very limited digital literacy but are supported by a high level of social capital. This last group of firms solves the challenges by finding partners who possess excellent digital capabilities. The qualitative case study method allows us to conduct in-depth and detailed analysis, but has thin generalizability. To address this limitation, future research can use a survey covering various industries to test the proposed theory that has resulted from this study, so that the generalizability can be assured.
Keywords: 650; digital technology; business model innovation; digital transformation; dynamic capability; organizational agility; learning organization; open innovation